Professional identities, conflicting positions, and the challenge of conducting mathematical discussions in professional learning communities - Heyd-Metzuyanim, Einat; Nachlieli, Talli (NOMAD Nordic Studies in Mathematics Education, 2024)
Our goal in this study is to examine the interweaving of identifying (identity authoring ) and mathematizing of teachers in a Professional learning community (PLC) as they engage with a mathematical challenge. We rely on commognition and positioning theory to examine how storylines of teacher-students interfered with teacher-leaders' ability to hear mathematical ideas that were unfamiliar to them. We focus on one PLC session and show how the conflicts in positions, where the teacher-leader fought to maintain the identity of a mathematical leader, led to ineffectiveness of the mathematical discussion. We argue for the necessity of affording PLC participants alternative roles that would not threaten their professional identity as competent mathematics teachers.